The Existence of Tin Placer Relation With Tin Belt In Kundur Waters Area Riau archipelago Province - Setiady, D; Syafri, I; Aryanto, N C D (Journal of physics. Conference series, 2019)
Placer mineral is mineral deposits that have channels transportation as particles of grains mineral in the river and on the ocean floor. The most common and plentiful placer mineral are rutile, tin, magnetite, ilmenite, zircon and many gems. The existence of ancient rivers flooded after the end of the ice age, of the ancient river many deposited heavy minerals from rocks around the island of Sumatra and Kalimantan. The existence of an ancient channel formed at the Holocene is thought to be a valley that has the potential as mineral deposits to be transported and deposited in the same time with the sediments that fill the valleys. Tin Gravel is one of the heavy minerals in Sunda shelf deposited above the ancient valleys of granite rock The type of granite in Sunda shelf is granite I type (east belt) and S type (middle belt). The granite belt (tin belt) is related to the heavy mineral associations found in the study area, whether derived from granite I type or granite S Type is still a subject of debate among researchers. The granite type classification is based on opaque minerals. The magnetite series comprises of: magnetite, ilmenite, hematite and pyrite, while the ilmenite series consists of: cassiterite, ilmenite, and graphite. Granite in Indonesia islands containing tin mineral included in the middle belt (type S), and east belt (type I). Occurred on a Carbon, Perm and also Triass age. Granites are distributed almost along the coastal to offshore of Kundur Island. Tin (SnO2), or tin include oxide group, brownish, prismatic. Tin deposited is associated with acid igneous rock formed on pegmatites accumulation. In Study area tin founded in 16 samples of seabed surface sediments with the largest content of 0.04124% and the smallest 44 of 0.0006%. The purpose of this study is to know the existence of placer tin content in marine sediments in Kundur waters, its relation with tin belt (granite type), whereas the purpose of the study is to know the source of tin placer.